Methodology of teaching in the military-patriotic spirit in general secondary education and specialized schools. (Eurasian Journal of Humanities and Social Sciences, 2022)
The decision on the measures to organize the activities of classes specialized in militarypatriotism in general secondary education and specialized schools and the methodology of teaching students in the spirit of military-patriotism at school.